Perbedaan Fonetik Bahasa Minangkabau di Kenagarian Sinuruik dan Kajai Kecamatan Talamau Kabupaten Pasaman Barat - B., Rahmadani; Agustina, Agustina; Amir, Amril (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this research to describe differences the Minangkabau language phonetic in Kenagarian Sinuruik and Kajai. This research is a qualitative with descriptive method. Informants study determined 8 people. The data collection of this research is through the method see, interviewing, recording and recordkeeping. Data analysis techniques in this study were (1) transcribing speech into written language, (2) inventory data from the recording to classify words with different pronunciation sounds/phonemes at the beginning, middle and end of words, (3) classify the difference sounds/phonemes the same word by local speakers, (4) make the conclusion. The results concluded that the differences in phonetics and pronunciation in the language of Minangkabau in Sinuruik and Kajai as follows. First, found 9 differences vocals. Second, found 12 differences consonants. Thirdly, found 3 differences diphthongs. Fourth, Found 3 different mixtures.